Discovery and preclinical evaluations of GST-HG131, a novel HBV antigen inhibitor for the treatment of chronic hepatitis B infection. (1st November 2022) - Hu, Yanbin; Sun, Fei; Yuan, Qiang; Du, Jinhua; Hu, Lihong; Gu, Zhengxian; Zhou, Qiong; Du, Xiaoting; He, Shibo; Sun, Ya; Wang, Qian; Fan, Lirong; et al.
Graphical abstract: Abstract: Chronic hepatitis B (CHB) remains a significant health challenge worldwide. The current treatments for CHB achieve less than 10% cure rates, majority of the patients are on therapy for life. Therefore, cure of CHB is a high unmet medical need. HBV surface antigen (HBsAg) loss and seroconversion are considered as the key for the cure. RG7834 is a novel, orally bioavailable small molecule reported to reduce HBV antigens. Based on RG7834 chemistry, we designed and discovered a series of dihydrobenzopyridooxazepine (DBP) series of HBV antigen inhibitors. Extensive SAR studies led us to GST-HG131 with excellent reduction of HBV antigens (both HBsAg and HBeAg) in vitro and in vivo . GST-HG131 improved safety in rat toxicology studies over RG7834. The promising inhibitory activity, together with animal safety enhancement, merited GST-HG131 progressed into clinical development in 2020 (NCT04499443).